88.7k views
5 votes
I could really use your help for problem #1​

I could really use your help for problem #1​-example-1
User Mutp
by
5.4k points

1 Answer

2 votes

Answer:


\large\boxed{ r=\sqrt{(GM_1M_2)/(F_g)}}

Explanation:


F_g=(GM_1M_2)/(r^2)\qquad\text{multiply both sides by}\ r^2\\\\F_gr^2=r^2\!\!\!\!\!\!\diagup\cdot(GM_1M_2)/(r^2\!\!\!\!\!\!\diagup)\\\\F_gr^2=GM_1M_2\qquad\text{divide both sides by}\ F_g\\\\(F_g\!\!\!\!\!\!\diagup r^2)/(F_g\!\!\!\!\!\!\diagup)=(GM_1M_2)/(F_g)\\\\r^2=(GM_1M_2)/(F_g)\Rightarrow r=\sqrt{(GM_1M_2)/(F_g)}

User Ben Greenman
by
5.0k points